The Influence of Liquidity, Solvency, And Foundation Size on Profitability with Perception-Based Financial Management as a Moderating Variable at the Al Istiqamah Integrated Education Foundation Balikpapan - Nur’ Ana, Andi; Defung, Defung; Wardhani, Wirasmi (Jurnal Pendidikan Indonesia, 2025)
This study aims to analyze the influence of liquidity, solvency and foundation size on profitability with perception-based financial management as a moderating variable at Yayasan Pendidikan Al Istiqamah Terpadu Balikpapan (YPAITB). The research employs a quantitative approach using a case study design, where primary data were collected through Likert-scale questionnaires distributed to 31respondents consisting of foundation leaders and financial managers. Data were analyzed using Moderated Regression Analysis (MRA) and complemented by a financial trend analysis covering the period 2014-2023. The results show that perceived liquidity and solvency have positive but insignificant effects in profitability, while foundation size (number of students) has a positive and significant effect, indicating that student growth contributes to operational surplus. Moreover, financial management does not moderated the relationships between liquidity, solvency and foundation size with profitability, suggesting that the moderating hypotheses are not supported. The trend analysis reveals that YPAITB’s liquidity and solvency remained relatively stable from 2014-2023, while profitability declined temporarily due to facility expansion and relocation but improved afterward as asset utilization became more efficient. The study concludes that effective financial management and student capacity growth are critical factors in sustaining financial performance in educational foundations. Theoritically, the findings reinforce the relevance of Financial Sustainability Theory and the Resource-Based View (RBV) in nonprofit contexts. Practically, the study recommends improving financial mangement competencies, strengthening technology-based governance, and focusing on student growth strategies to enhance long-term financial sustainability.